Respostas
respondido por:
1
Explicação passo-a-passo:
cos x= cateto adjacente/hipotenusa
a)cos f = 3/x
0,6 = 3/x
0,6.x = 3
x = 3/0,6
x = 5
para descobrir y, uso Pitágoras.
a² = b² + c²
5² = y² + 3²
25 =y² +9
y² = 16
y= √16 = 4
b) tg = cateto oposto/cateto adjacente
tg s = x /1
7/6 = x/1
6x = 7.1
6x =7
x = 7/6
y² = 1² + (7/6)²
y² = 1 + 49/36
y²= 36 +49/36
y² = 85/36
y = √85/6
c) Sen = cateto oposto/ hipotenusa
Sen a = x/2
3/5 = x/2
5x = 2.3
5x = 6
x = 6/5
2² = (6/5)² + y²
4 = 36/25 + y²
y² = 4 - 36/25
y² 100 - 36/25
y² =64/25
y =√64/√25
y= 8/5.
d) cos b = x/y
1/2 = x/y
y= 2x
(2x)² = 3² + x²
4x² = 9 + x²
4x² - x² = 9
3x² =9
x² = 9/3
x² = 3
x = √3. y = 2x
y = 2(√3) =2√3.
gabiemtgata:
Obrigado kk agora sim entendi
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás